REPRESENTASI CITRA DIRI JOKOWI DALAM FILM “JOKOWI” REPRESENTATION OF JOKOWI’S SELF-IMAGE IN FILM “JOKOWI” - Afifah Noor Khairani; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Self-image is a view of a self portrait or the ideal projection traits of an individual. Imaging in the context of politics becomes an important part of things affects perception, emotion, feeling, consciousness, and public opinion, so that the community can be crammed into a reference, source, choice, and certain decisions. The film, part of the mass media, has the power that is capable of delivering, socializing, even manipulating the meaning or message which is displayed in the audio and visual, currently considered by the politicians as a media campaign implied. Docu-drama movie which takes the theme of a person's biography has started popping up, one of them titled "JOKOWI" has been pretty much showing self-image of Joko Widodo as Jokowi who is a phenomenal politician currently. The research also aims to find out how is representation of Jokowi’s self-image in the film "JOKOWI".This research uses qualitative descriptive methods which were analyzed through by semiotics of Roland Barthes. Data collection techniques has been used in this research were observation of audio and visual display in the film "JOKOWI", documentations, as well as the interview which is the statements delivered by using by purposive sampling techniques.The results of this research show that there is a representation of Jokowi’s self-image in the film JOKOWI i.e. the ideal characteristics owned by Jokowi such as honesty, a sense of tolerance, simple, ingenious and keep his promise, never give up. Through by validity data process, it can be said that this movie is a representation of the real Jokowi’s self-image, but there are several informants in this study says different opinion. That is because of his inconsistent state has been done by Jokowi himself in reality to show himself image. One of it, Jokowi has been less fulfilled his promise and also simple performance.Keywords : Representation, Self-image, Politician, Jokowi, Biography Film